The Role of Community in Improving Cultural Understanding: An International KPM Experience Study in 4 Villages in Kedah Malaysia - Ayang Kia Dermawan; Harri Santoso; Rosnidawati Rosnidawati; Mohammad Shaharuddin; Zharifa Yasmin; Dara Assyifa; Wildan Shafly; Mahda Alhaq; Hasrarul Zikri; Arkas Tri Maulana; Fina Marlina (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Cultural understanding between 2 countries will be able to strengthen the bonds of brotherhood between 2 related countries, Indonesia and Malaysia. This community service aims to increase the role of the community in cultural understanding between 2 related countries. This International Community Service Lecture (KPM) was held for 14 days in four villages in Negeri Kedah, Malaysia: Taman Permatang Katong, Keda Tepi Sungai Village, Kampung Kuala Dulang Kecil, and Taman Permai Utama. With several activities carried out including; psychoeducation for the elderly, teenagers and children, mutual cooperation and joint activities between KPM International participants and communities in 4 villages. The main findings identified the role of the community in cultural understanding, there are three key elements, namely: (1) preservation and application of local traditions in welcoming newcomers, (2) active involvement of community leaders in facilitating integration, and (3) consistent culture of hospitality. Consistency in honoring guests, including the welcoming tradition to leaving, has a significant impact on the positive experiences of participants and the effectiveness of the program. Challenges such as language and cultural differences can be overcome through creativity and openness. This community service concludes that the strength of the community and local wisdom, especially in the tradition of honoring guests, is key in creating a sense of togetherness and facilitating effective integration in understanding the cultures of the people of the 2 countries. These findings provide important insights for designing future community service programs, highlighting the importance of collaboration with local communities and utilizing traditions in facing integration challenges in the era of globalization.Pemahaman budaya antar 2 negara akan mampu mengeratkan tali persaudaraan antara 2 negara serumpun Indonesia dan Malaysia. Pengabdian masyarakat ini bertujuan untuk meningkatkan peran komunitas dalam pemahaman budaya antar 2 masyarakat negara serumpun. Kuliah Pengabdian Masyarakat (KPM) Internasional ini dilaksanakan selama 14 hari di empat desa Negeri Kedah, Malaysia : Taman Permatang Katong, Desa Keda Tepi Sungai, Kampung Kuala Dulang Kecil, dan Taman Permai Utama. Dengan beberapa kegiatan yang dilakukan antara lain; Psikoedukasi terhadap lansia, remaja dan anak-anak, Gotong royong serta kegiatan bersama antara peserta KPM Internasional dan komunitas di 4 desa. Temuan utama mengidentifikasi peran komunitas dalam pemahaman budaya terdapat tiga elemen kunci dalam yaitu: (1) Pelestarian dan penerapan tradisi lokal dalam menyambut pendatang, (2) Keterlibatan aktif tokoh masyarakat dalam memfasilitasi integrasi, dan (3) Budaya keramahtamahan yang konsisten. Konsistensi dalam memuliakan tamu, termasuk tradisi penyambutan hingga pelepasan, memberikan dampak signifikan terhadap pengalaman positif peserta dan efektivitas program. Tantangan seperti perbedaan bahasa dan budaya dapat diatasi melalui kreativitas dan keterbukaan. Pengabdian masyarakat ini menyimpulkan bahwa kekuatan komunitas dan kearifan lokal, terutama dalam tradisi memuliakan tamu, adalah kunci dalam menciptakan rasa kebersamaan dan memfasilitasi integrasi yang efektif dalam pemahaman budaya masyarakat 2 negara. Temuan ini memberikan wawasan penting bagi perancangan program pengabdian masyarakat di masa depan, menyoroti pentingnya kolaborasi dengan komunitas lokal dan pemanfaatan tradisi dalam menghadapi tantangan integrasi di era globalisasi.